INFORMATION AND COMMUNICATION TECHNOLOGIES AS TOOLS FOR IMPROVING STUDENTS’ MOTIVATION TO LEARNING - Matviichuk, Л.А. (Journal of Information Technologies in Education (ITE), 2020)
The purpose of the study is to determine the effectiveness of the use of computer tools in the educational process, including electronic journals of student achievement in pedagogical and technical higher education institutions. The role of information and communication technologies in the life of the modern student. Influence of electronic tools on formation of consciousness of the future specialist in the chosen field. Conditions of application of modern technologies in educational establishments of Ukraine are investigated. During the experiment, questionnaires were applied (before and after the experiment), testing (before and after the experiment). The reliability of the Cronbach questionnaire was 0.87. 107 respondents from different Ukrainian educational institutions participated in the study. The survey established the level of motivation of students to get a higher education. The conditions of using modern technologies in Ukrainian educational establishments are determined. The effect of electronic journals on the quality of academic achievement of students of technical and pedagogical specialties was experimentally tested. Positive changes were identified, increasing students' interest in the course, using e-journals during the educational process. The results of the study emphasize that students who have access to the group's e-journal of success, monitor their results, have the opportunity to evaluate their own underperformance and increase their personal rating. Low level of students' motivation is determined. Factors that influence the teacher-student-teacher feedback have been identified. The conditions that contribute to improving the comfortable environment during the students' study are considered. The pedagogical experiment shows that electronic tools help to build lasting feedback in knowledge transfer, increase student productivity in learning. The study found that a considerable number of students receive higher education only to receive the so-called «crust», which in their opinion, in the future will allow to get a good position. It should be noted that students are becoming more aware of the latest technologies every year. A number of measures for organizing a comfortable environment for students' study in the modern dimension are highlighted.